Mid-term follow-up of a fractured flow diverter in the internal carotid artery - Janos S. Gellen, MD; Johannes A.R. Pfaff, MD, MHBA (Radiology Case Reports)
Flow-diverting stents are an established endovascular treatment for internal carotid artery (ICA) dissections, but their long-term durability remains a concern, particularly in cases involving mechanical stress. A 40-year-old male with Eagle syndrome presented with a minor stroke due to left ICA dissection and underwent successful flow-diverter placement. While initial follow-up was unremarkable, subsequent imaging revealed stent fractures at 3 and 7 months, leading to complete ICA occlusion by 8 months. Despite this, the patient remained asymptomatic due to robust collateral circulation. Two-year follow-up imaging confirmed stable ICA occlusion, no new ischemic lesions, and scattered stent fragments in the subarachnoid space, which were best visualized with susceptibility-weighted MRI. This case underscores the potential for delayed stent fractures and asymptomatic ICA occlusion in Eagle syndrome, highlighting the importance of advanced imaging in long-term follow-up and the need for further research on stent durability in high-stress vascular regions.